Citra Perusahaan yang Memediasi Pengaruh Green Marketing dan Digital Sustainability Terhadap Green Consumer Decision pada Jasa Pelayanan di PT Pos Indonesia (Persero) - Telah, Nola Christiane; Pradiani, Theresia; Ruspitasari, Widi Dewi (Dinasti Research, 2025)
In recent years, environmental issues and sustainability have become major considerations in consumer decision-making, particularly in the service sector. This study aims to examine the influence of green marketing and digital sustainability on green consumer decision, with corporate image acting as a mediating variable. The object of this research is PT Pos Indonesia (Persero) Denpasar Branch, a state-owned enterprise undergoing a transformation toward environmentally friendly operations through various initiatives, such as the use of electric vehicles, service digitalization, and paper reduction. The study employs a quantitative approach with an explanatory research design. Data were collected from 84 respondents who are customers of PT Pos Indonesia Denpasar Branch and met specific criteria, such as environmental awareness and usage of the company’s digital services. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS software. The results indicate that both green marketing and digital sustainability have a significant positive effect on corporate image. Furthermore, corporate image significantly influences green consumer decisions. Corporate image is also proven to mediate the relationship between green marketing and digital sustainability with green consumer decision. These findings suggest that a positive corporate image strengthens the effectiveness of sustainable marketing strategies and digital initiatives in shaping consumer decisions. The practical implication of this study highlights the importance of integrating sustainability principles into marketing and digital strategies to build consumer trust, loyalty, and preference. Academically, this study also fills a gap in the literature regarding the simultaneous influence of green marketing and digital sustainability within the context of service companies in developing countries.